Low-temperature electrolyte and preparation method and application thereof
By using linear carboxylic acid ester and nitrile mixture and 3-fluorotoluene in the lithium-ion battery electrolyte, combining lithium salt and film-forming additives, a stable SEI is solved, and the problem of poor performance of lithium-ion batteries in low temperature environments is solved. , improves the ionic conductivity and compatibility of the battery and significantly improves the low-temperature charging and discharge performance.
Patent Information
- Application Number
- CN202411358971.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium-ion batteries have poor performance in low temperature environments, mainly due to the poor compatibility of linear carboxylic acid esters and nitrile solvents with graphite, resulting in a decrease in ionic conductivity and increased viscosity, which limits the application range of the battery.
Linear carboxylic acid esters and nitrile mixtures are used as solvents for the electrolyte, and 3-fluorotoluene is added to form a stable solid electrolyte interface (SEI) in combination with lithium salt and film-forming additives to improve the ionic conductivity of the electrolyte and graphite compatibility.
It significantly improves the reversible charging and discharging performance of lithium-ion batteries at low temperatures, reduces the interface impedance, expands the application temperature range of the battery, and improves the electrochemical stability of the electrolyte.
Smart Images

Figure CN119208739A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery electrolytes, and more specifically to a low-temperature electrolyte and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in portable electronic products and electric vehicles due to their advantages such as high energy / power density and long cycle life. As the electric vehicle market continues to expand, the performance requirements for them are also getting higher and higher. However, the performance of batteries strongly depends on regional and seasonal changes. Especially in low temperature environments, the performance of lithium-ion batteries is not ideal, which has become a major technical problem that currently restricts the development of the electric vehicle market. Ethylene carbonate (EC) can form a stable solid electrolyte interface (SEI) on the graphite surface to protect graphite and improve the cycle performance of the battery. Therefore, it is considered to be an indispensable component of commercial lithium-ion battery electrolytes. However, EC has a high freezing point of 34°C. As the temperature decreases, the ionic conductivity of EC-based electrolytes decreases sharply and the viscosity increases, resulting in rapid battery capacity decay. At the same time, due to the severe hindrance of graphite lithium insertion dynamics at low temperatures, the capacity of lithium-ion batteries is not only significantly reduced when charged at low temperatures, but also there are safety hazards caused by lithium precipitation. At present, the use of most lithium-ion batteries at low temperatures is limited to low-temperature discharge after charging at room temperature, which greatly limits the application range of lithium-ion batteries.
[0003] Li + Liquid phase transport and interfacial reaction kinetics are considered to be the key factors limiting the low temperature performance of lithium-ion batteries. + The transport in the electrolyte is mainly affected by the viscosity and the degree of dissociation of lithium salts. The interfacial reaction mainly includes Li + Desolvation, migration in SEI and charge transfer process. Therefore, designing an electrolyte with high ionic conductivity, low desolvation energy and low SEI impedance is an effective means to improve the low-temperature performance of lithium-ion batteries. Linear carboxylates and nitrile solvents have low freezing points (<-40°C), low viscosity and moderate dielectric constants, and are considered to be ideal low-temperature electrolyte solvents. However, linear carboxylates and nitrile solvents have poor reduction stability, decompose at higher potentials, and the generated products cannot effectively protect graphite, resulting in the battery not being able to work properly. Therefore, solving the compatibility problem of linear carboxylates and nitrile solvents with graphite is the key to exerting their low-temperature advantages and improving the low-temperature performance of lithium-ion batteries. Summary of the invention
[0004] The present invention provides a low-temperature electrolyte and a preparation method and application thereof, which are used to solve the problem in the prior art that linear carboxylic acid esters and nitrile solvents in lithium ion battery electrolytes are not compatible enough with graphite, resulting in unsatisfactory battery performance in a low-temperature environment.
[0005] In a first aspect, the present invention provides a low-temperature electrolyte comprising the following components: electrolyte solute lithium salt, organic solvent, electrolyte additive and 3-fluorotoluene; wherein the organic solvent is a mixture of linear carboxylic acid esters and nitriles in a volume ratio of 1:0.25 to 4.
[0006] As a possible implementation manner, the concentration of the electrolyte solute lithium salt in the low-temperature electrolyte is 0.5-5 mol / L; and / or, the volume ratio of the organic solvent in the low-temperature electrolyte is 10%-79.9%; and / or, the volume ratio of the additive in the low-temperature electrolyte is 0.1%-10%; and / or, the volume ratio of the 3-fluorotoluene in the low-temperature electrolyte is 20%-80%.
[0007] Exemplarily, the concentration of the electrolyte solute lithium salt in the low-temperature electrolyte is 0.5 to 3 mol / L; and / or, the volume ratio of the organic solvent in the low-temperature electrolyte is 10% to 50%; and / or, the volume ratio of the additive in the low-temperature electrolyte is 3% to 10%; and / or, the volume ratio of the 3-fluorotoluene in the low-temperature electrolyte is 40% to 80%.
[0008] As a possible implementation, the electrolyte solute lithium salt is one or a combination of sulfonyl imide lithium salts, phosphate lithium salts, and boric acid lithium salts; and / or the linear carboxylic acid ester is any one or a combination of any two or three of ethyl acetate, methyl acetate, methyl butyrate, and methyl propionate; and / or the nitrile is any one or a combination of any two or three of acetonitrile, propionitrile, butyronitrile, valeronitrile, isobutyronitrile, and isovaleronitrile; and / or the electrolyte additive is fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), lithium nitrate (LiNO 3 ), lithium difluorophosphate (LiPO 2 F 2 ) and lithium difluorooxalatoborate (LiODFB) or a combination of some or all of them.
[0009] As a possible implementation, the electrolyte solute lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), or a combination of any two thereof.
[0010] In a second aspect, the present invention provides a method for preparing a low-temperature electrolyte, comprising the following steps: mixing the raw material components in proportion to the formula components contained in the low-temperature electrolyte described in any possible implementation method of the first aspect to obtain the low-temperature electrolyte.
[0011] In a third aspect, the present invention provides the use of the low-temperature electrolyte described in any possible implementation of the first aspect in a lithium-ion battery.
[0012] In a fourth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode plate, a separator, an electrolyte and a negative electrode plate, wherein the electrolyte is the low-temperature electrolyte described in any possible implementation of the first aspect.
[0013] As a possible implementation manner, the positive electrode plate, the separator, the electrolyte and the negative electrode plate are assembled in sequence, wherein the capacity ratio of the negative electrode plate to the positive electrode plate is 1 to 1.3:1.
[0014] As a possible implementation method, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder are uniformly mixed in the positive electrode solvent to form a positive electrode slurry, the slurry is coated on the positive electrode collector, and dried to obtain the positive electrode sheet; wherein the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 70-95:5-20:5-20; and / or, the negative electrode active material, the negative electrode conductive agent and the negative electrode binder are uniformly mixed in the negative electrode solvent to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and dried to obtain the negative electrode sheet; wherein the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 70-95:5-20:5-20.
[0015] As a possible implementation, the positive electrode active material is selected from LiCoO 2 、LiFePO 4 、LiMn 2 O 4 、LiNi x Co y Mn z Al 1-x-y-z O 2 , wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z≤1, one or more thereof; and / or, the negative electrode active material is selected from one or more of a carbon material, an alloy negative electrode, and a conversion reaction material. Exemplarily, the carbon material is any one of artificial graphite, natural graphite, hard carbon, and soft carbon; the alloy negative electrode is any one of Si, Sn, Sb, Bi, Sn, and Sb; the conversion reaction material is any one of a transition metal oxide, sulfide, phosphide, and selenide; the transition metal is any one of Ni, Mn, Fe, Co, V, Cu, and Ti.
[0016] The low-temperature electrolyte provided by the present invention uses a mixture of linear carboxylic acid esters and nitrile compounds as solvents to replace conventional carbonate solvents. Since linear carboxylic acid esters and nitrile solvents have low freezing points (<-40°C), low viscosity and moderate dielectric constants, they reduce the melting point and viscosity of the electrolyte and effectively improve the ionic conductivity of the electrolyte at low temperatures. The present invention utilizes lithium salts and film-forming additives to decompose to form a stable SEI to inhibit the decomposition of linear carboxylic acid esters and nitrile compounds, thereby improving the compatibility of linear carboxylic acid esters and nitrile solvents with graphite negative electrodes; the inorganic-rich SEI formed reduces the interfacial impedance and significantly improves the Li + The transport dynamics in SEI effectively improve the reversible charge and discharge performance of lithium-ion batteries in low temperature environments.
[0017] The present invention adopts 3-fluorotoluene to construct a local high concentration in the low-temperature electrolyte provided by the present invention, thereby avoiding the problem of excessively high viscosity of high-concentration lithium salts, and 3-fluorotoluene has the advantages of a wide liquid range (-111 to 116° C.) and high electrochemical stability, and has higher practicality and safety than hydrofluoroethers; at the same time, the constructed local high-concentration electrolyte enables more anions to participate in the solvation structure, promotes the desolvation process, and effectively improves the low-temperature charging performance of the lithium ion battery; the present invention adopts 3-fluorotoluene to construct a local high-concentration electrolyte, and lithium salt anions replace solvent molecules to participate in the solvation first sheath, thereby reducing the desolvation energy, accelerating the desolvation process, and improving the kinetic process of lithium ion embedding into graphite. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 This is a graph showing the change in ionic conductivity of electrolytes A to I as a function of temperature provided in an embodiment of the present invention.
[0020] Figure 2 The charge and discharge curves of button batteries A to I provided in the embodiments of the present invention at room temperature and different current densities (1C=372mAh / g) are shown.
[0021] Figure 3 The charge and discharge curves of button battery A provided in an embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0022] Figure 4The charge and discharge curves of button battery B provided in an embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0023] Figure 5 The charge and discharge curves of the button battery C provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0024] Figure 6 The charge and discharge curves of the button battery D provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0025] Figure 7 The charge and discharge curves of the button battery E provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0026] Figure 8 The charge and discharge curves of the button battery F provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0027] Fig. 9 The charge and discharge curves of the button battery G provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0028] Fig.10 The charge and discharge curves of the button battery H provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown.
[0029] Fig.11 The charge and discharge curves of the button battery I provided in the embodiment of the present invention at -20°C and different current densities (1C=372mAh / g) are shown. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In order to solve the problem in the prior art that the linear carboxylic acid ester and nitrile solvents in the lithium ion battery electrolyte are not compatible with graphite, resulting in unsatisfactory battery performance in a low temperature environment, the embodiment of the present invention provides a preparation experiment of a low-temperature electrolyte and tests its conductivity, verifying that the low-temperature electrolyte provided by the embodiment of the present invention has a wide liquid range and still has a high ionic conductivity at -60°C.
[0032] The low-temperature electrolyte provided by the present invention adopts a mixture of linear carboxylates and nitriles as solvents instead of conventional carbonate solvents. Since linear carboxylates and nitrile solvents have a low freezing point (<-40°C), low viscosity and a moderate dielectric constant, they reduce the melting point and viscosity of the electrolyte and effectively improve the ionic conductivity of the electrolyte at low temperatures.
[0033] Furthermore, the present invention provides an experiment to test the conductivity and electrochemical properties of a low-temperature electrolyte, which verifies that the low-temperature electrolyte provided by the present invention has significant application advantages at low temperatures and has better electrochemical properties.
[0034] The present invention utilizes lithium salt and film-forming additive to decompose to form a stable SEI to inhibit the decomposition of linear carboxylic acid esters and nitrile compounds, thereby improving the compatibility of linear carboxylic acid esters and nitrile solvents with the graphite negative electrode; the formed inorganic-rich SEI reduces the interface impedance and significantly improves the Li + The transport dynamics in SEI effectively improve the reversible charge and discharge performance of lithium-ion batteries in low temperature environments.
[0035] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0036] Example 1
[0037] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0038] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 10:40:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte A.
[0039] Example 2
[0040] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0041] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 40:10:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte B.
[0042] Example 3
[0043] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0044] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 15:5:5:80, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte C.
[0045] Comparative Example 1
[0046] This embodiment provides an experiment for preparing a common electrolyte.
[0047] In a glove box, ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1, and then bis(fluorosulfonyl)imide lithium salt was added to make the final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte D.
[0048] Comparative Example 2
[0049] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0050] In a glove box, ethyl acetate, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 50:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte E.
[0051] Comparative Example 3
[0052] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0053] In a glove box, ethyl acetate, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 50:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte F.
[0054] Comparative Example 4
[0055] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0056] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and PTE were mixed in a volume ratio of 10:40:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte G.
[0057] Comparative Example 5
[0058] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0059] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 8:42:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to make a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte H.
[0060] Comparative Example 6
[0061] This embodiment provides a preparation experiment of a low-temperature electrolyte.
[0062] In a glove box, ethyl acetate, butyronitrile, fluoroethylene carbonate, and 3-fluorotoluene were mixed in a volume ratio of 42:8:10:40, and then bis(fluorosulfonyl)imide lithium salt was added to a final concentration of 1 mol / L. The mixture was stirred for 12 h and mixed evenly to obtain electrolyte I.
[0063] Experimental Example 1
[0064] This experimental example provides an experiment to test the conductivity of the electrolyte.
[0065] Stainless steel was used as the positive and negative electrodes respectively, and the electrolyte sample to be tested was added as the electrolyte to prepare a stainless steel||stainless steel symmetric battery.
[0066] In this experimental example, the electrolytes A to I prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were used as the electrolyte samples to be tested, respectively, to prepare symmetrical batteries A to I, and their impedances were tested. The formula σ = d / (R s ×A) to calculate the conductivity, where σ represents the conductivity in S / cm; R s is the resistance value obtained by the test, in Ω; A is the electrode area, in cm 2 ; d is the thickness of the battery, in cm. Figure 1 The results shown. Figure 1 It can be seen that the electrolyte A prepared in Examples 1 to 3 has a wide liquid range and still has a high ionic conductivity at -60°C. The ionic conductivity of the electrolyte D prepared in Comparative Example 1 drops sharply below -20°C, which is related to the coagulation of the electrolyte caused by the high freezing point of ethylene carbonate. It can be seen that the low-temperature electrolyte prepared by the method provided by the present invention has significant application advantages at low temperatures. Comparative Example 3 shows high ionic conductivity, which is related to the high lithium salt solubility of nitrile solvents. The other comparative examples all show ionic conductivities lower than those of the embodiments.
[0067] Experimental Example 2
[0068] This experimental example provides an experiment to test the electrochemical performance of the electrolyte.
[0069] Graphite powder, conductive agent and binder were mixed in a mass ratio of 8:1:1 to prepare a graphite electrode, which was used as the working electrode, lithium as the counter electrode, and the electrolyte to be tested was added to assemble a lithium-ion half-cell (graphite||Li) button cell. The rate performance was tested under constant current charge and discharge conditions in the voltage range of 0.01 to 2V; after 5 cycles at room temperature at a current density of 0.5C, the low-temperature charge and discharge capacity was tested at -20°C at different current densities.
[0070] In this experimental example, the electrolytes A to I prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were used as the electrolytes to be tested to prepare button batteries A to I, so as to test their rate performance and low-temperature charge and discharge capacity. Figure 2 The charge and discharge curves of button cells A to I at different current densities (1C = 372 mAh / g) at room temperature, and Figures 3 to 11 And the results are shown in Table 1, where Figures 3 to 11 They are the charge and discharge curves of button batteries A to I at -20°C and different current densities (1C=372mAh / g).
[0071] Table 1 Electrochemical performance test results (mAh / g)
[0072]
[0073] From Table 1 and Figure 2 It can be seen that the application performance of the electrolytes prepared in Examples 1 to 3 in the battery is significantly better than that of the comparative example; at a high current density of 5C, the reversible charge and discharge capacities of the electrolytes prepared in Examples 1 to 3 are all above 200 mAh / g.
[0074] From Table 1 and Figures 3 to 11 It can be seen that the electrolytes prepared in Examples 1 to 3 have excellent low-temperature charge and discharge performance. Under the charge and discharge conditions of -20°C and 0.1C, their reversible charge and discharge capacities are significantly higher than those of the comparative example.
[0075] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0076] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A low-temperature electrolyte, characterized in that: The invention comprises the following components: electrolyte solute lithium salt, organic solvent, electrolyte additive and 3-fluorotoluene; Wherein, the organic solvent is a mixture of linear carboxylic acid esters and nitriles in a volume ratio of 1:0.25-4.
2. The low-temperature electrolyte according to claim 1, characterized in that: The concentration of the electrolyte solute lithium salt in the low-temperature electrolyte is 0.5 to 3 mol / L; And / or, the volume ratio of the organic solvent in the low-temperature electrolyte is 10% to 50%; And / or, the volume ratio of the additive in the low-temperature electrolyte is 3% to 10%; And / or, the volume ratio of the 3-fluorotoluene in the low-temperature electrolyte is 40% to 80%.
3. The low-temperature electrolyte according to claim 1, characterized in that: The electrolyte solute lithium salt is one or a combination of sulfonimide lithium salt, phosphate lithium salt, borate lithium salt; And / or, the linear carboxylic acid ester is any one or a combination of any two or any three of ethyl acetate, methyl acetate, methyl butyrate and methyl propionate; And / or, the nitrile is any one or a combination of any two or any three of acetonitrile, propionitrile, butyronitrile, valeronitrile, isobutyronitrile and isovaleronitrile; And / or, the electrolyte additive is one or a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, lithium nitrate, lithium difluorophosphate and lithium difluorooxalatoborate.
4. The low-temperature electrolyte according to claim 1, characterized in that: The electrolyte solute lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide, or a combination of any two thereof.
5. A method for preparing a low-temperature electrolyte, characterized in that: The steps include: The low-temperature electrolyte is obtained by mixing the raw material components in proportion according to the formula components contained in the low-temperature electrolyte according to any one of claims 1 to 4.
6. Use of the low-temperature electrolyte according to any one of claims 1 to 4 or the low-temperature electrolyte prepared by the preparation method according to claim 5 in a lithium-ion battery.
7. A lithium ion battery, characterized in that: It comprises a positive electrode plate, a separator, an electrolyte and a negative electrode plate, wherein the electrolyte is the low-temperature electrolyte according to any one of claims 1 to 4 or the low-temperature electrolyte prepared by the preparation method according to claim 5.
8. A method for preparing a lithium ion battery according to claim 7, characterized in that: The positive electrode sheet, the separator, the electrolyte and the negative electrode sheet are assembled in sequence to obtain the lithium-ion battery; wherein the capacity ratio of the negative electrode sheet to the positive electrode sheet is 1 to 1.3:
1.
9. The preparation method according to claim 8, characterized in that: The positive electrode active material, the positive electrode conductive agent and the positive electrode binder are uniformly mixed in the positive electrode solvent to prepare a positive electrode slurry, and the slurry is coated on the positive electrode collector and dried to obtain the positive electrode sheet; wherein the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 70-95:5-20:5-20; And / or, the negative electrode active material, the negative electrode conductive agent and the negative electrode binder are uniformly mixed in the negative electrode solvent to prepare a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and dried to obtain the negative electrode sheet; wherein the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 70-95:5-20:5-20.
10. The preparation method according to claim 9, characterized in that: The positive electrode active material is selected from LiCoO2, LiFePO4, LiMn2O4, LiNi x Co y Mn z Al 1-x-y-z O2, one or more of 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z≤1; And / or, the negative electrode active material is selected from one or more of carbon materials, alloy negative electrodes, and conversion reaction materials.
Citation Information
Patent Citations
Ultralow-temperature lithium ion battery electrolyte and preparation method thereof
CN113270642A
Lithium ion battery electrolyte, preparation method thereof and lithium ion battery
CN114361583A
High concentration lithium ion electrolytes for battery cells
CN116914244A
Battery electrolyte and preparation method thereof
CN117996181A
Additives for lithium secondarty battery withcharge-cutoff voltages over 4.35
KR1020060077506A
Cited By
Electrolyte for low-temperature lithium battery
CN121416610A
Non-aqueous electrolyte and power storage device
WO2026164029A1
